Iron and Steel : Class, Race, and Community in Birmingham, Alabama, 1875-1920 - McKiven, Henry M. (Book collections on Project MUSE., 1995)
This study of Birmingham's iron and steel workers unravels the complex connections between race relations and class struggle that shaped the city's social and economic order. It also traces the links between the process of class formation and the practice of community building and neighbourhood politics. According to the author, the white men who moved to Birmingham soon after its founding to take jobs as skilled iron workers shared a free labour ideology that emphasized opportunity and equality between white employees and management at the expense of less skilled black labourers.